Fault-tolerant control of a double star induction machine operating in active redundancy - Guizani, S.; Nayli, A.; Ben Ammar, F. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Scientific novelty. To increase the availability of the variable speed drive, an original control strategy for reintegrating the repaired faulty inverter is implemented to allow the repaired inverter to resume operation of the drive motor. This strategy control is based on the specific use of FOC to resynchronize the output frequency of the repaired inverter with the motor speed. Results. The results demonstrated the value of vector control in each star power supply system to avoid transient over currents at the input of the 2nd converter, by synchronizing the frequency of the 2 converters to the rotor speed. Practical value. An experimental model around a DSIM is set up to validate the active redundancy operation of the system. Active redundancy provides the variable speed drive with an increase in the reliability of the variable speed drive and significantly improves the availability rate of the driven load, since the disconnection of one of the 2 converters following a failure does not affect the operation of the machine.

Наукова новизна. Для підвищення готовності перетворювача частоти реалізовано оригінальну стратегію управління для повторного підключення відремонтованого несправного перетворювача, що дозволяє відремонтованому перетворювачу відновити роботу приводного двигуна. Ця стратегія управління заснована на специфічному використанні FOC для повторної синхронізації вихідної частоти відремонтованого перетворювача зі швидкістю двигуна. Результати продемонстрували цінність векторного управління в кожній зіркоподібній системі електропостачання для запобігання перехідним струмам на вході другого перетворювача шляхом синхронізації частоти двох перетворювачів зі швидкістю ротора. Практична цінність. Створено експериментальну модель на основі DSIM для перевірки роботи системи в режимі активного резервування. Активне резервування забезпечує підвищення надійності перетворювача частоти і значно покращує коефіцієнт готовності навантаження, оскільки відключення одного з двох перетворювачів після відмови не впливає на роботу машини.
Keywords: double star induction machine; active redundancy; field-oriented control; reliability; асинхронна машина з подвійною зіркою; активне резервування; полеорієнтоване управління; надійність